Radicalism and Reformism in Political Controversy Tories in Great Britain in First Third of 19th Century - V. V. Klochkov; V. S. Nazarova; M. A. Ponomareva (Научный диалог, 2022)
A radical and reformist discourse on the nature and limits of the “folk element” in the British political system in the first third of the 19th century is considered. The key features of this discourse and the role it played in shaping a broad Tory identity are studied. It is shown that during the period under study, the focus of political controversy shifted from issues of sovereignty and royal prerogative to issues related to fair popular representation and the nature of the necessary political reforms. The novelty of the study lies in the emphasis on the fact that it was the abuse of power by the “popular element” in the British constitutional system that was the main threat to sustainable development. This thesis is supported by documentary evidence, including those first introduced into scientific circulation. It is emphasized that the broad Tory identity that developed during the period under study was based on adherence to the ideals of the constitutional order, established as a result of the Glorious Revolution. The author’s assessment of how the various approaches of the Tory groups to the issue of reform eroded the broad identity of the Tories, creating a basis for the formation of political ideas of conservatism, is presented.